KEDUDUKAN DAN PERAN HAKIM TUNGGAL DALAM KONSEP PLEAS WITHOUT BARGAINS DI INDONESIA DAN TIONGKOK - Oktaviana, Deka (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract The increasing number of cases entering the judiciary system each year has led to the accumulation of the workload that judges must handle. The emergence of the paradigm of the judiciary as a 'dumpster